ChemInform Abstract: Palladium‐Catalyzed Construction of Spirooxindoles by Arylative Cyclization of 3‐(γ, δ‐Disubstituted)allylidene‐2‐Oxindoles. Issue 31 (August 2015) - Kim, Ko Hoon; Moon, Hye Ran; Lee, Junseong; Kim, Jae Nyoung
Abstract The title reaction follows an oxidative Heck arylation, allylic palladium migration, aryl C—H bond functionalization/arylation sequence.